Interferon‐β–Induced Injury During Pediatric Muscle Differentiation: Insight Into Juvenile Dermatomyositis Pathogenesis - Lauren T. Covert; Alaa Osman; George A. Truskey (ACR Open Rheumatology)
Objective Juvenile dermatomyositis (JDM) involves up‐regulated type I interferons (IFNs), including IFNβ, yet pathologic mechanisms remain poorly understood. We aimed to characterize the functional and structural effects of IFNβ on in vitro human pediatric myoblast growth and differentiation in a three‐dimensional skeletal muscle model (myobundles). Methods Myobundles fabricated from myoblasts of a healthy pediatric donor were exposed to IFNβ at 0 to 5,600 IU/mL during growth (days 1–4), differentiation (days 4–11), and/or mature (days 11–18) periods. To assess myobundle structure and function, contractile force, kinetics, and fatigue were measured at day 18 with subsequent immunohistochemistry. Results Myobundles were not functionally affected by IFNβ exposure during growth period alone. However, when IFNβ exposure continued through differentiation, myobundles became dysfunctional (P < 0.0001). IFNβ during differentiation or mature periods alone resulted in dose‐dependent decreases in contractility, with greater decrease in the differentiation alone group (P < 0.0001). Twitch kinetics and fatigue remained largely unchanged when myobundles were exposed to IFNβ only during growth, yet twitch time slowed (P < 0.005) and fatigue decreased (P < 0.002) when myobundles were exposed during differentiation or mature stages alone. Nuclei density and myofiber size and organization also decreased when IFNβ was added during differentiation period alone. Conclusion IFNβ decreases pediatric myobundle contractile function most significantly during differentiation of myoblasts to myotubes. Function is not affected when IFNβ exposure is limited to myoblast proliferation alone. These findings implicate a pathologic role for IFNβ in JDM by impairing myoblast differentiation, leading to subsequent loss of function and ongoing need for muscle regeneration and repair.